2020
DOI: 10.1002/adfm.202004733
|View full text |Cite
|
Sign up to set email alerts
|

Building Functional Memories and Logic Circuits with 2D Boron Nitride

Abstract: The fast development of synthesis routes and preparation technology of 2D materials has motivated a rapid growth in the micro‐ and nanoelectronic memory devices, which gives rise to the breakthroughs in the semiconductor research area. Hexagon boron nitride (h‐BN) with excellent chemical, mechanical, and optical properties has been proven to have potential in overcoming the scaling limit to nanometer, and even sub‐nanometer lengths to replace the use of thick and stiff blocking dielectrics in two‐terminal or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 315 publications
(436 reference statements)
0
26
0
Order By: Relevance
“…[ 27 ] The recent reports on resistive‐switching materials have shown a great potential in h ‐BN‐based devices. [ 28,29 ] Therefore, further research on threshold switching (TS) and artificial synaptic devices based on h ‐BN material is highly desirable for the realization of emerging neuromorphic computing systems. [ 30 ]…”
Section: Figurementioning
confidence: 99%
“…[ 27 ] The recent reports on resistive‐switching materials have shown a great potential in h ‐BN‐based devices. [ 28,29 ] Therefore, further research on threshold switching (TS) and artificial synaptic devices based on h ‐BN material is highly desirable for the realization of emerging neuromorphic computing systems. [ 30 ]…”
Section: Figurementioning
confidence: 99%
“…[ 24–28 ] In particular, hexagonal boron nitride (hBN), which has dielectric properties and tunable atomic thickness (i.e., layered materials), allows us to extend van der Waals (vdW) heterostructure FETs with 2D materials to demonstrate various functional memories and logic circuits. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BN exhibits an adjustable electronic structure after interface engineering modification, which is conducive to electrocatalytic reactions. [9,[183][184][185] Li and co-workers demonstrated that a graphene-BN (G/BN) heterostructure can be used as an effective metal-free catalyst for the ORR. [186] By combining two different substances with similar lattice parameters and crystal structures, G/BN possesses unique structural characteristics and exhibits distinct physical and chemical properties from those of pure BN and graphene.…”
Section: Heterostructure and Defectsmentioning
confidence: 99%